Integrasi AI dalam Penyusunan Modul Ajar: Tinjauan Kritis terhadap Nilai-nilai Pedagogis - Fika Anjana (LPPM IAIN Sorong, 2026)
This study aims to describe the utilization of Artificial Intelligence (AI) as a supporting tool for teachers in developing teaching modules and to examine its implications for pedagogical values. The background of this research lies in the increasing use of AI in educational settings, which has the potential to enhance teachers’ work efficiency but also poses challenges in maintaining pedagogical integrity. This research employed a qualitative approach using a case study design involving three informants: a teacher, a vice principal for curriculum affairs, and a principal. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the Miles and Huberman model. The findings indicate that teachers are at various stages of AI adoption, ranging from initial exploration to the integration of pedagogical values. AI functions as a digital mediating tool that supports teacher creativity; however, some of its applications remain instrumental and instantaneous. In conclusion, AI can strengthen teacher professionalism if applied reflectively and humanistically, while keeping pedagogical values as the main foundation of teaching practice.